Diagnostic Challenge Of Peritoneal Tuberculosis In Woman With Ascites - Nenci Siagian; Muhammad Vitanata Arfijanto (Biomolecular and Health Science Journal, 2020)
Tuberculosis (TB) is a major health global issue including extrapulmonary tuberculosis (EPTB). The one of manifestation of EPTB is peritoneal TB that constitutes 2% from all cases of pulmonary TB around the world. The diagnosis of peritoneal TB is quite challenging because many cases have symptom that similar to other diseases and those often necessary need further specific examinations such as PCR, culture and radiologic examination. We reported a case report of peritoneal tuberculosis in woman with ascites.